Altered peripheral profile of blood cells in Alzheimer disease: A hospital-based case-control study. Issue 21 (May 2017) - Chen, Si-Han; Bu, Xian-Le; Jin, Wang-Sheng; Shen, Lin-Lin; Wang, Jun; Zhuang, Zheng-Qian; Zhang, Tao; Zeng, Fan; Yao, Xiu-Qing; Zhou, Hua-Dong; Wang, Yan-Jiang
Abstract : Abstract: Alzheimer disease (AD) has been made a global priority for its multifactorial pathogenesis and lack of disease-modifying therapies. We sought to investigate the changes of profile of blood routine in AD and its correlation with the disease severity. In all, 92 AD patients and 84 age and sex-matched normal controls were enrolled and their profiles of blood routine were evaluated. Alzheimer disease patients had increased levels of mean corpuscular hemoglobin, mean corpuscular volume, red cell distribution width-standard deviation, mean platelet volume, and decreased levels of platelet distribution width, red blood cell, hematocrit, hemoglobin, lymphocyte, and basophil compared with normal controls. Alterations in quantity and quality of blood cells may be involved in the pathogenesis of AD and contribute to the disease progression.